THE INFLUENCE OF GAMMA IRRADIATION ON THE ACTIVITY OF THE BREZY SECRETOR AND THE ENZYME HOMEOSTASIS OF THE MEAD. - Kodirov Shokir Kodirovich, Sevaraxon Kuranova Saidolimovna,Yunusov Muxammadabror Abdumannob o’g’li, Boqiyeva Ibodatxon Vaxabjonovna, Dumayeva Zuxra Nasirdinovna, Salomov Shoxabbos Nozimjon ugli (South Eastern European Journal of Public Health, 2025)
A chronic experiment was conducted on rats. In these experiments, the influence of irradiation on the activity of subdural enzyme secretion was studied. According to the results obtained, gamma radiation suppresses the synthesis of enzymes (amylase, lipase, and proteases) and proteins in the pancreas depending on the dosage.